Practicality of problem-based mathematics worksheets assisted by GeoGebra to enhance students’ mathematical conceptual understanding - Fitri, Yosi Cahyaningtiyas; Jupri, Al; Zetriuslita (Proceedings of International Conference on Research in Education, 2025)
Problem-Based Learning (PBL) is an instructional model that uses authentic problems. Integrating PBL with GeoGebra promotes active engagement and exploration of mathematical concepts. It also helps develop creativity and supports the use of critical thinking skills in problem solving. This combined approach leads to a more comprehensive understanding of mathematics. Effective implementation requires a structured strategy. Instructional tools must be accessible to both teachers and students throughout the process. This study aims to identify and describe the practicality of student worksheets (LKPD). The research method used in this study is Research and Development (R&D), following the ADDIE model. Although the ADDIE model consists of 5 stages, this research only consists of 3 stages, namely the analysis, design stages and development stages, as it aims to describe the practicality of the instructional tools. Practicality was carried out by teachers and students. The results showed that the device, on average, received a positive response from students and teachers. These instructional tools are designed for Grade XI senior high school students. The practicality results indicate that LKPD also received an excellent rating across all assessed aspects. Therefore, the LKPD is deemed suitable to improve the mathematical concept understanding of students.